(untitled) (LEARNing Landscapes, 2016)
This paper explores a partnership between a high school, university researchers, and community artists in the service of improved student learning, empowerment, and self-expression through the urban arts. The Urban Arts Project partners teachers at James Lyng high school with hip-hop and other urban artists to develop units across the curriculum, supported by subject-area specialists from McGill’s Faculty of Education. In this article, we introduce the project and what we have learned about processes of school reform through cross-sectoral collaboration from the rst year of our partnership. This includes sharing the perspectives of the teachers and artists most actively involved in the rst year’s initiatives (with video interview links).